2023
DOI: 10.1097/prs.0000000000010145
|View full text |Cite
|
Sign up to set email alerts
|

E2F1- deficient adipose-derived stem cells improve skin wound closure in mice by upregulating paracrine expression of VEGF and TGF-β1

Abstract: Background: Wound healing is a widespread health problem that imposes a financial burden on health systems. Cell therapy with genetically modified adipose-derived stem cells (ADSCs) is a promising strategy for dysregulated wound repair. E2F transcription factor 1 (E2F1) is a bidirectional regulator of cytokines. Here, the authors aimed to investigate the impact and potential mechanism of E2F1–/– ADSCs in promoting the wound healing process. Methods: Forty-five C57BL/6 mice (specific pathogen-free, male) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 38 Our previous research found that ADSCs from E2F1 –/– mice promoted wound healing via enhancing VEGF and TGF-β1 paracrine. 21 Besides, E2F1 knockout was protective in myocardial ischemia and skin injury. 39 , 40 MiRNAs participate in various biological processes through post-transcriptional regulation, and miRNA expression can be regulated by transcription factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 Our previous research found that ADSCs from E2F1 –/– mice promoted wound healing via enhancing VEGF and TGF-β1 paracrine. 21 Besides, E2F1 knockout was protective in myocardial ischemia and skin injury. 39 , 40 MiRNAs participate in various biological processes through post-transcriptional regulation, and miRNA expression can be regulated by transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 Besides, we also emphasized E2F1 deficiency could improve the ability of ADSC paracrine to promote wound healing. 21 Exosomal microRNAs (miRNAs) are considered to be important paracrine substances for ADSCs in promoting wound healing. 22 E2F1 can regulate the transcription of multiple miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue healing: ADSCs can accelerate wound healing and/or improve healing by promoting angiogenesis, particularly in chronic wounds [154,161]. Their regenerative and immunomodulatory properties contribute to cell proliferation and accelerate wound healing and cutaneous regeneration [162][163][164][165].…”
Section: Regenerative Features and Utility In Tissue Engineeringmentioning
confidence: 99%